ROSYJSKI TRZECI SEKTOR WE WSPÓŁCZESNEJ FEDERACJI ROSYJSKIEJ - Lachowicz, Marta (Studia Europaea Gnesnensia, 2018)
At present, Russian Federation shows symptoms of departure from democratization processes and civil society models. Over the last decade, Vladimir Putin’s coming to power, changes in the strategy and rhetoric of internal affairs in demonstrated tendencies for increased social control, restrictions imposed on NGOs and deliberate restructuring of the third sector in line with the designs of the central authority.